Co-precipitation synthesis of CuCo2O4 nanoparticles for supercapacitor electrodes with large specific capacity and high rate capability. (20th November 2021) - Sun, Mengxuan; Fang, Qisheng; Li, Zhijie; Cai, Chao; Li, Hao; Cao, Baobao; Shen, Wenzhong; Liu, Terence Xiaoteng; Fu, YongQing
Highlights: CuCo2 O4 nanoparticles were synthesized using a facile co-precipitation method, and they showed. 1 large surface area and high porosity. 2 CuCo2 O4 electrodes exhibited both battery-type and capacitive-type behavior. 3 high specific capacity and good rate capability. 4 CuCo2 O4 –250//AC asymmetric supercapacitor showed good electrochemical performance. Abstract: Ultra-fine CuCo2 O4 nanoparticles were synthesized using a facile co-precipitation method assisted by NaBH4 and CTAB, and they were explored as supercapacitor electrode material to achieve a large specific capacity and a high rate capability. The synthesized CuCo2 O4 –250 nanoparticles had a large surface area of 159.6 m 2 g − 1, which provided numerous active sites to enhance their specific capacity. The abundant mesopores with a pore volume of 0.3599 cm 3 g − 1 effectively provided numerous channels for the electrolyte ions to diffuse onto the active surface of nanoparticles. The CuCo2 O4 –250 nanoparticles based electrodes exhibited both battery-type and capacitive-type behavior in the charging/discharging processes. It achieved a large specific capacity of 401.2 C g − 1 at a current density of 0.5 A g − 1 in 2 M KOH electrolyte. Results showed that when the current density was increased from 1 A g − 1 to 10 A g − 1, a retained specific capacity of 77.5% was achieved, indicating a good rate capability. An asymmetric supercapacitor with CuCo2 O4 –250 nanoparticles and activated carbon as positive and negative electrodes exhibited a high energy density of 29.5 Wh kg −1 at a power density of 832.6 W kg −1 and a capacity retention of 72.7% at 10 A g − 1 after 10, 000 cycles. Graphical abstract: Image, graphical abstract